Is It A Good Move To Release Policy Of Making English Language As Optional Subject In Elementary School? - Nina Afria Damayanti; Laila Ramlan; Woro Endah Sitoresmi; Muhammad Takwin Machmud (ELEMENTARY SCHOOL JOURNAL PGSD FIP UNIMED, 2023)
Merdeka Curriculum or in Indonesian Language known as Kurikulum Merdeka is widely considered as the most popular curriculum applied in many educational institutions in Indonesia. In the context of elementary school, Merdeka curriculum places English Language as an optional subject offered to students. In fact, nowadays students as the future generation live in the digitized and network based community where English plays a critical role to help them adapt to the rapid change of technology and science. Consequently, it is crucial to study this government policy in the Merdeka curriculum on the English language subject for elementary students. This study aims to analyze the government policy on placing the English language as an optional subject in elementary school using the theory of language development and the role of English as lingua franca in the 21st century. This study applies a library research method and data are collected from published and unpublished scientific articles, analytical journals, government reports and national scale newspapers that are relevant to the aims of the study.Keywords: Merdeka Curriculum, English Languange, Elementary School